Istikhdām Wasā'il al Sharā'ih fi ta'līm Mahārat al Kalam bi Ma'had Rīhan al Jannah Pasar Maga Mandailing Natal - Syaipuddin Ritonga (IAIN Padangsidimpuan, 2022)
The use of the slide method in teaching speaking skills at the Rayhanul al-Janah Islamic Boarding School, Pasir Maga, Mandling Natal. Slide are teaching tools that use the senses of sight and hearing. Teaching speaking skills requires many tools and aids, and one of the effective ways to teach speech is slide. The problem in this research is how to use slide in teaching speaking skills at the Rohan al-Janah Islamic Boarding School, Pasir Maga, Mandling Natal. The purpose of this research is to determine the use of slide in teaching speaking skills at the Rohan al-Janah Islamic Boarding School, Pasir Maga, Mandling Natal, In terms of the application of the use of slide, the advantages and disadvantages of slide, and the results of teaching speaking skills through slide. The research method in this research is qualitative analytical field research. The results of this study are that slide has an effect on improving speaking skill, and slide are an effective means of teaching speaking skill. Slide has advantages and disadvantages, and help them to teach speaking skill. The conclusion of this study is that the use of slide in teaching can improve speaking skill